Cairo’s informal waste collectors: a multi-scale and conflict sensitive perspective on sustainable livelihoods - Didero, Maike (ERDKUNDE, 2012)
While waste management is a serious problem for many rapidly growing megacities in the global south, inhabitants in Cairo used to benefit from a comparatively well-functioning waste removal system. The Zabbaleen – informal waste collectors – have been collecting household waste since the beginning of the last century. In the 1990s however, this informal waste collection system started to become unable to cope with the rapidly increasing volume of waste generated by Cairo’s inhabitants. Hence, in 2003 the city administration commissioned several European multinationals to take over the waste removal. This decision deprived the Zabbaleen of their previous entitlement to the waste, their main source of income. Based on qualitative interviews conducted in two Zabbaleen settlements in 2006 and 2011, this article explores the long-term consequences of this reform decision. The sustainable livelihood framework is used to evaluate the impact of the reform on the Zabbaleens’ livelihoods. Although the Zabbaleen have utilized creative and flexible strategies to adapt to the new situation, their degree of vulnerability has increased considerably. In addition, the reform also failed to achieve the aim of an ecologically, economically, and socially sustainable waste management system. Drawing on insights derived from Bourdieu’s theory of social fields helps to explain this disastrous outcome. Focusing on the competition and power relationships between all actors implicated in Cairo’s waste management system, the analysis reveals that although the waste management system in Cairo is indeed a field in which the “global” and the “local” interact vehemently, the outcome of this interaction can only be explained by taking into account the intermediate national and local actors as well as the specific rules applying to the Egyptian political and economic field.